2007
DOI: 10.1021/es063061r
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence of a Linear Relationship between Inorganic Mercury Loading and Methylmercury Accumulation by Aquatic Biota

Abstract: Developing effective regulations on mercury (Hg) emissions requires a better understanding of how atmospheric Hg deposition affects methylmercury (MeHg) levels in aquatic biota. This study tested the hypothesis that MeHg accumulation in aquatic food webs is related to atmospheric Hg deposition. We simulated a range of inorganic Hg deposition rates by adding isotopically enriched Hg(II) (90.9% 202Hg) to 10-m diameter mesocosms in a boreal lake. Concentrations of experimentally added ("spike") Hg were monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 35 publications
2
72
0
1
Order By: Relevance
“…3). Previous studies have shown that, on the short term, there is a proportional response of rates of production (24,25) and bioaccumulation (26) of new methylmercury to new additions of inorganic mercury. However, when new mercury is added to a system that already contains older inorganic mercury, both the new and older mercury contribute to methylation (although not necessarily equally), so on the short term the overall rate of mercury methylation (new ϩ old) does not respond in direct proportion to the amount of new mercury added.…”
Section: Resultsmentioning
confidence: 99%
“…3). Previous studies have shown that, on the short term, there is a proportional response of rates of production (24,25) and bioaccumulation (26) of new methylmercury to new additions of inorganic mercury. However, when new mercury is added to a system that already contains older inorganic mercury, both the new and older mercury contribute to methylation (although not necessarily equally), so on the short term the overall rate of mercury methylation (new ϩ old) does not respond in direct proportion to the amount of new mercury added.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative interpretation could be that most of the standing oceanic inventory is not bioavailable; with a small and rapidly cycling pool of bioavailable Hg, inputs that are quickly converted to bioavailable forms could produce a rapid biotic response proportional to the input, as they do in lakes (see ref. [89]). However, this interpretation is not supported by MeHg inventory calculations for the Arctic Ocean, which lead to the striking finding that most of the MeHg already in the upper Ocean is not accumulated by marine biota, i.e.…”
Section: Lessons About the Fulcrums Controlling Biological Hg Trendsmentioning
confidence: 99%
“…Sources of Hg in these basins include historical gold and cinnabar mines, releases from chemical manufacturing and coal-fired power plants, atmospheric deposition, and wetlands (Rudd 1995;Brumbaugh et al 2001;Eisler 2004;Paller et al 2004;Warner et al 2005). Orihel et al (2007) demonstrated that organic mercury deposited directly to aquatic ecosystem was readily converted to methylmercury, which is available to biota. This relationship may explain the high fish concentrations and associated risk of mercury in the southeastern United States and Yukon River Basin, where mercury methylation rates are known to be high (Brumbaugh et al 2001).…”
Section: Dieldrin -Mink Dieldrin -Bald Eaglementioning
confidence: 99%